Исследование и разработка макета многозондового контактного устройства - Назаренко, Р. В. (ХНУРЭ, 2012)
It is presented developed the multiprobe contact device for the electric control of multilayered switching boards with high density arrangement of controllable elements.
Keywords: разработка макета; многозондовое контактное устройство